2022
DOI: 10.1007/s11207-022-02006-4
|View full text |Cite
|
Sign up to set email alerts
|

Rate of Change of Large-Scale Solar-Wind Structure

Abstract: Quantifying the rate at which the large-scale solar-wind structure evolves is important for both understanding the physical processes occurring in the corona and for space-weather forecast improvement. Models of the global corona and heliosphere typically assume that the ambient solar-wind structure is steady and corotates with the Sun, which is generally expected to be more valid at solar minimum than solar maximum, but this has not been well tested. Similarly, assimilation of solar-wind observations into mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 80 publications
0
2
0
Order By: Relevance
“…As solar wind structure is expected to be primarily a function of solar cycle phase (e.g. Owens, 2020), we also construct a solar activity index (SAI, Owens et al, 2022), aimed at characterising the progression of the solar cycle independent of the variation in sunspot cycle amplitude:…”
Section: Near-earth Solar Wind Datamentioning
confidence: 99%
“…As solar wind structure is expected to be primarily a function of solar cycle phase (e.g. Owens, 2020), we also construct a solar activity index (SAI, Owens et al, 2022), aimed at characterising the progression of the solar cycle independent of the variation in sunspot cycle amplitude:…”
Section: Near-earth Solar Wind Datamentioning
confidence: 99%
“…As the solar wind structure is expected to be primarily a function of the solar cycle phase (e.g. Owens, 2020), we also construct a solar activity index (SAI, Owens et al, 2022), aimed at characterising the progression of the solar cycle independent of the variation in sunspot cycle amplitude:…”
Section: Near-earth Solar Wind Datamentioning
confidence: 99%
“…In global heliospheric solar wind simulations, it was also found that the solar wind variability is strongly correlated with the solar cycle, with the corona and heliosphere being more variable at the solar maximum. However, limiting the analysis of the simulations to the solar equatorial region strongly reduces the difference between solar maximums and minimums (Owens et al 2022).…”
Section: Introductionmentioning
confidence: 99%